Edukasi MPASI dalam Program GERBANG EMAS: Membangun Pondasi Nutrisi Awal untuk Mencegah Stunting - Kusmawati, Iffah Indri; Putri, Noviyati Rahardjo; Megasari, Anis Laela; Larasati, Disa; Rahmah, Ulinuha Aufa; Ningrum, Dita Cahaya (Jurnal Kreativitas Pengabdian Kepada Masyarakat (PKM), 2025)
ABSTRACT Stunting is a health problem in toddlers characterized by height below the standard and delayed cognitive development as a result of chronic malnutrition. One of the contributing factors is inappropriate complementary feeding (CF) practices, in terms of timing, type, texture, and feeding frequency. A lack of maternal knowledge is a key factor underlying these inappropriate practices. This community service activity aimed to improve mothers’ knowledge regarding appropriate complementary feeding to support optimal child growth and development and to prevent stunting. The method was carried out through CF education, accompanied by examples of local menus and tips on food texture according to the child’s age, and concluded with a discussion. The target participants of this activity were 35 mothers of infants aged 6–12 months. Based on the pre-test results, the average maternal knowledge score was 7.8, which increased to 8.4 after the educational intervention. The results indicate an improvement in knowledge gained through participatory education in the complementary feeding class. It is expected that future activities will be complemented by long-term assistance, periodic evaluation of children’s nutritional status, and expanded research coverage that includes maternal behavior and involves a control group. Keywords: Complementary Feeding, Stunting, Health Education  ABSTRAK Stunting merupakan masalah kesehatan pada balita yang ditandai dengan tinggi badan di bawah standar dan keterlambatan perkembangan kognitif akibat kekurangan gizi kronis. Salah satu penyebabnya adalah praktik pemberian MPASI yang tidak tepat, baik dari segi waktu, jenis, tekstur, maupun frekuensi makan. Kurangnya pengetahuan ibu menjadi faktor utama dalam ketidaktepatan tersebut. Kegiatan pengabdian masyarakat ini bertujuan untuk meningkatkan pengetahuan ibu mengenai pemberian MPASI yang tepat guna mendukung tumbuh kembang anak secara optimal dan mencegah stunting. Metode kegiatan dilakukan melalui pemberian edukasi MPASI disertai dengan contoh menu lokal serta tips tekstur makanan sesuai dengan usia anak lalu ditutup dengan diskusi. Mitra dalam kegiatan ini adalah 35 orang ibu balita usia 6 -12 bulan. Berdasarkan hasil pre test didapatkan rerata nilai pengetahuan ibu adalah 7,8 dan meningkat menjadi 8,4 setelah intervensi edukasi. Hasil menunjukkan adanya peningkatan pengetahuan yang didapatkan melalui edukasi partisipatif dalam kelas MPASI. Diharapkan untuk kegatan selanjutnya dapat dilengkapi dengan pendampingan jangka panjang, evaluasi status gizi anak secara berkala, serta perluasan cakupan penelitian yang mencakup perilaku ibu dan melibatkan kelompok kontrol. Kata Kunci: MPASI, Stunting, Edukasi Kesehatan